La paradoja del desarrollo: consultas comunitarias en la posguerra guatemalteca - Vaclav Masek (Revista Iberoamericana de Estudios de Desarrollo)
Resistance against state-sponsored capitalist extractivism in Latin America has been invigorated by a multi-scalar alliance of indigenous and environmental movements enacting new forms of democratic participation. How do these movements draw on the most painful past as a source of inspiration to persist in their organizing, even in the face of systematic exclusion? Eleven months of patchwork ethnography —in-person and digital participant observation— with an indigenous rights organization in Guatemala empirically reveal the deployment of narrative mechanisms as part of their cultural repertoire to concert strategic actions. The emblematic case of the ongoing struggle for «free, prior, and informed consent» consultation in the lake town of El Estor over the oldest mineral mine in Guatemala shows the unfolding of civic action through temporal imaginations —a narrative reconstruction of how social movements imagine themselves in history and position themselves in time—. Connecting three layers of meaning-making through the collective memory of colonialism, genocide, and extractivism, Maya Q’eqchi community leaders articulate «future-coordination» through collective memory. An array of direct actions also serves to resist the State, implicating scholarly reconceptualizations of indigenous territory, post-conflict development, and the political ambiguities of organizing.